TITIK SINGGUNG WEWENANG MAHKAMAH AGUNG DENGAN MAHKAMAH KONSTITUSI - Isra, Saldi (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2015)
The mixing of authority between the Constitutional Court and the Supreme Court has raised a range of issues. In turn, there is the contact authority of the two institutions which could lead to the occurrence of legal uncertainty. In connection with the authority testing regulations, for example, although the Supreme Court and the Constitutional Court have the same right to testÂ the legislation, but with different types and hierarchy of legislation being tested, then the interpretation of the rules of the legislation for which they were these institutions must be subject to a hierarchical system of laws and regulations that apply. Therefore, the validity of the norm is derived from the legislation is higher. Moreover, any decision of the judicial review of the UUD, this decision is erga omnes, including for judges of the Supreme Court and judges of the court under the Supreme Court.Keywords : Authority, Constitutional Court, Supreme Court